Effects of water nutrient concentrations on stream macroinvertebrate community stoichiometry: a large-scale study - Beck, Miriam; Billoir, Elise; Usseglio-Polatera, Philippe; Meyer, Albin; Gautreau, Edwige; Danger, Michael (Peer Community Journal)

(untitled)
Basal resources generally mirror environmental nutrient concentrations in the elemental composition of their tissue, meaning that nutrient alterations can directly reach consumer level. An increased nutrient content (e.g. phosphorus) in primary and detrital resources under nutrient enriched conditions should favour taxa with a high demand for this nutrient. With the nutrient demand of a taxon being correlated to the elemental composition of its body tissue (e.g. phosphorus content), such above described species shifts likely alter the overall community stoichiometry. However, studies addressing stoichiometry at community level are rare and most often restricted to lacustrine planktonic systems, single streams or limited experimental setups. Relying on a stoichiometric database for >200 taxa and >1300 standardized sampling events of macroinvertebrate assemblages from the French national monitoring programme, we investigated the effect of water phosphorus and nitrogen load on stream macroinvertebrate community stoichiometry. Community stoichiometry was significantly affected by water phosphorus concentration and the effect was strongest at low levels of nitrogen. While we could not confirm our hypothesis of increasing community %P (and decreasing C:P, N:P) with increasing water phosphorus concentrations for the overall community, it clearly followed this pattern for both Insecta and Malacostraca. General differences in the elemental composition among major taxonomic groups and a shift among these groups over the nutrient gradient probably explain the response of community stoichiometry. Our results show that assumptions from Ecological Stoichiometry Theory also hold at the community level, at least for two dominant taxa, and on a large spatial scale, with likely consequences for nutrient cycling and ecosystem function.